Effects of non-invasive respiratory support on gas exchange and outcomes in COVID-19 outside the ICU. (August 2021) - Gough, Ciara; Casey, Michelle; McCartan, Thomas A.; Franciosi, Alessandro N.; Nash, Derek; Doyle, Dominic; Hyland, Neil; Kavanagh, Grace; Toland, Sile; Powell, Caleb; O'Regan, Rhea; Conluain, Ruán Ó.; et al.
Abstract: Non-invasive respiratory support (NRS) outside of the ICU has played an important role in the management of COVID-19 pneumonia. There is little data to guide selection of NRS modality. We present outcomes of NRS outside the ICU and discuss the effects of NRS on gas exchange with implications for management. Highlights: Use of CPAP and HFNC may avoid intubation and allow time for recovery in COVID-19. SpO2 :FiO2 correlates well with P:F and can risk stratify without invasive testing. Bedside assessment of respiratory rate and work of breathing outside ICU is important.